2006
DOI: 10.1089/vbz.2006.6.32
|View full text |Cite
|
Sign up to set email alerts
|

Natural Tick-Borne Encephalitis Virus Infection among Wild Small Mammals in the Southeastern Part of Western Siberia, Russia

Abstract: Infestation of small mammals, including common shrews Sorex araneus L., field mice Apodemus agrarius Pallas, and red voles Clethrionomus rutilus Schreber, with immature Ixodes persulcatus ticks and their infection with tickborne encephalitis virus (TBEV) were studied in the forest-steppe habitat in the vicinity of Novosibirsk, Russia. Larval ticks parasitize all three host species, but virtually all nymphs were found only on field mice and red voles. Detection of the viral RNA using reverse transcription (RT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 19 publications
2
41
0
6
Order By: Relevance
“…The analysis of only 333 sera from rodents captured in 2006 Ð2007 allowed us to detect the presence of anti-TBEV antibodies at three out of four (Thun, Belp, Kiesen, but not at Trimstein) sites in Switzerland whereas in a previous study, the screening of 9,986 ticks by RT-PCR (Thun: n ϭ 2,001; Belp: n ϭ 2,117; Kiesen: n ϭ 4,230; (Burri et al 2011). A small proportion of rodents displayed anti-TBEV antibodies, ranging from 1.6 to 9.9%, but these results are consistent with results from Kozuch et al (1967) and Bakhvalova et al (2006) who reported antibody prevalence of 4 Ð11% and 2.6 Ð10.2%, respectively. Interestingly, although more rodents were captured in 2007, seroprevalence in rodent was lower than in 2006.…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of only 333 sera from rodents captured in 2006 Ð2007 allowed us to detect the presence of anti-TBEV antibodies at three out of four (Thun, Belp, Kiesen, but not at Trimstein) sites in Switzerland whereas in a previous study, the screening of 9,986 ticks by RT-PCR (Thun: n ϭ 2,001; Belp: n ϭ 2,117; Kiesen: n ϭ 4,230; (Burri et al 2011). A small proportion of rodents displayed anti-TBEV antibodies, ranging from 1.6 to 9.9%, but these results are consistent with results from Kozuch et al (1967) and Bakhvalova et al (2006) who reported antibody prevalence of 4 Ð11% and 2.6 Ð10.2%, respectively. Interestingly, although more rodents were captured in 2007, seroprevalence in rodent was lower than in 2006.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, Germany seems to be a country of low TBE risk in comparison to a prevalence of 61% in rodents of a high endemic area in Siberia (Bakhvalova et al 2006). This rating is supported by the low incidence of human TBE cases in Germany compared with other European countries, for example, the Czech Republic or Russia (Donoso Mantke et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…They are widespread in most ecological systems, have a small home range, are easy to trap and monitor, and are heavily parasitized by ticks, which probably results in higher TBE virus prevalence (and thus lower associated costs) than in ticks. Once infected with TBEV, they are supposed to develop a persistent infection , Nuttall et al 1994, Danielova et al 2002, Sü ss 2003, Bakhvalova et al 2006, Gray et al 2009, Kiffner et al 2011.…”
mentioning
confidence: 99%
“…Probably, the number of FE-TBEV strains present was too small to form a stable viral population and there was competition from endemic S-TBEV strains. Evidence for the long-term persistence of TBEV in populations of small rodents without ticks was provided by the vertical transmission of TBEV between generations of these animals (Bakhvalova et al, 2006(Bakhvalova et al, , 2009. Comparable data are missing for large mammals and birds.…”
mentioning
confidence: 99%